Cognitive Behavioral Therapy With Religious and Spiritual Clients: A Critical Perspective. Issue 4 (1st October 2016) - Carlson, Kathryn M.; González-Prendes, A. Antonio
ABSTRACT: Religion and spirituality (R/S) are important factors in the lives of many individuals. Yet, R/S and their impact on mental health are topics that are often overlooked in clinical practice. We offer a critical perspective on the integration of R/S in cognitive-behavioral therapy (CBT). We discuss factors that have contributed to the relative lack of attention to R/S in mainstream psychotherapies in general and CBT in particular, and examine the use of CBT with R/S clients. We suggest ways to conceptualize and adapt CBT strategies, including mindfulness, so that they can be effectively used with R/S clients.